Pro .NET 2.0 XML - Joshi, Bipin (Apress, 2012)
The Internet has brought a huge difference in the way we develop and use software applications. Applications are becoming more and more distributed, connecting heterogeneous systems. With such a radical change, the role of XML is highly significant. XML has already established itself as a standard way of data encoding and transfer. No wonder that Microsoft’s .NET Framework provides such a strong support for XML. Data access, raw parsing, configuration, code documentation, and web services are some of the examples where .NET harnesses the power and flexibility of XML.